Combining participatory mapping with Q-methodology to map stakeholder perceptions of complex environmental problems. (January 2015) - Forrester, John; Cook, Brian; Bracken, Louise; Cinderby, Steve; Donaldson, Andrew
Abstract: It is readily accepted that understanding socio-environmental challenges requires consideration of multiple stakeholder perspectives and knowledge claims. But a largely ignored question is 'how best to analyse those competing perspectives and claims?'. This paper explores the development of one GIS-based methodology – and reports on its application – to understand and map stakeholder knowledge. We find that combining Q-methodology with participatory mapping helps to overcome a significant problem in social engagement: representing the unclear connection between what people say or do and their underlying attitudes, values or beliefs . The paper is based on a reflexive engagement with flood management and natural adaptive capacity in the Scottish-English Borderlands. The paper confirms how such topics can benefit from an appreciation of the wide range of stakeholders' positions, as well as the underlying beliefs informing those positions. Most importantly, we provide an account of our methodology, offering a template for others interested in unpacking complex socio-environmental issues. Highlights: A mixed methods approach explores the problem of representing the connection between what people say or do and their underlying beliefs. Offer a pathway to reconciling and integrating social factors with their spatial context. Forcing participants (nicely) to confront their personal interpretation and/or worldviews. Help participants and researchers confront their own perspectives as part of reflexive research process.